Cardiovascular effects of airborne particulate matter: A review of rodent model studies. (March 2020) - Hadei, Mostafa; Naddafi, Kazem
Abstract: In recent year, animal models have been growingly used to increase our knowledge about the toxicity of PM and underlying mechanisms leading to cardiovascular diseases. In this article, we review the current state of knowledge and findings of studies investigating the cardiovascular effects of PM in rats and mice. The six main areas covered in this review include: I) nature of particulate matter and toxicity mechanisms, II) systemic inflammation, III) heart rate and heart rate variability, IV) histopathological effects, V) atherosclerosis, VI) thrombosis, and VI) myocardial infarction. This review showed that animal model studies have been successful to bring new insights into the mechanisms underlying PM-induced cardiovascular diseases. However, there are some areas that the exact mechanisms are still unclear. In conclusion, investigating the cardiovascular effects of PM in vivo or interpreting the results should attempt to justify the role of different PM compositions, which may vastly affect the overall cytotoxicity of particles. Highlights: We reviewed cardiovascular studies on rodent models. Animal models have been successful study PM-induced cardiovascular diseases. There are some areas that the exact mechanisms are still unclear. in vivo studies should account for the role of different PM compositions.